Influence Android-Based Learning to Self -Regulated Learning, Entrepreneurship, and Mathematical Literacy - Dewi Surani; Mamay Komarudin; Nugrahini Kusumawati; Jaka Wijaya Kusuma (AL-ISHLAH: Jurnal Pendidikan, 2021)
The Covid-19 pandemic requires students to study online and at home. Online learning has its challenges because educators must choose suitable media in delivering material. This study aims to find a comparison of learning independence, entrepreneurial spirit and mathematical literacy before and after using Android media. This research method uses quantitative methods with pre and post group design. This research was conducted in one of the junior high schools in Serang on social arithmetic material. The instrument used is a learning independence questionnaire and an entrepreneurship spirit questionnaire. Another instrument is a mathematical literacy test. Data analysis used paired sample t-test. The conclusion from the results of this study is that there are differences in learning independence, entrepreneurial spirit and mathematical literacy before and after using android media.